Investigating CPAP Compliance in Patients with Obstructive Sleep Apnea - Önay, Övsen; Mutlu, Hasan; Emre Süslü, Ahmet; Metin Önerci, Tevfik (ENT Updates, 2018)
Objective: Our aim in this study is to investigate, in patients who are advised to use CPAP, the rate of usage, differences between the patients who use the device and those who don’t; and the factors affecting the compliance rates. Methodology: A telephone survey was applied to the patients who underwent polysomnography, between the years 2010 -2015 and were thereafter advised to use CPAP as the treatment method. Results: Total number of patients included in the study was 108. Of them, 77 (71%) was male and 31 (29%) was female. The mean age was 50 (±11). There were 47 (43,5%) patients with comorbidities. Of 108 patients, 63 (58%) reported using CPAP at the time of the survey and 45 (42%) reported having abandoned the treatment, 62% (n: 28) of this 45 patients reported that they ceased the CPAP use within the first week of their treatment. Of 63 patients using CPAP, 3 (5%) was found noncompliant while 60 (95%) was found compliant. Conclusion: In our study, rate of CPAP use was found to be 55%. The difference between the mean ages of CPAP users and non-users was found statistically significant (p: 0,008). the results of our study suggests that BMI is not a factor that affects the rate of CPAP use. In our study, contrary to what would be expected, the mean CPAP pressure of the patients using the device were found to be higher than that of non-users.